Clinical Analysis of Childhood Acute Lymphoblastic Leukemia With Epilepsy Seizures - Li, Rui; Tang, Ji-Hong; Zhang, Bing-Bing; Shi, Xiao-Yan; Dai, Yuan-Yuan; Qu, Rui (Frontiers in Neurology, 2022)
Objective: In order to analyze the clinical characteristics of epileptic seizures in children with acute lymphoblastic leukemia ( ALL ) during treatment. Methods: The clinical and imaging data of children diagnosed as ALL with epilepsy seizures from January 2013 to December 2020 were retrospectively analyzed. Results: A total of 2217 children with ALL were admitted during the study, of whom 229 ( 10.33 % ) had epileptic seizures after ALL treatment. Among them, 45 ( 19.65 % ) were in the high-risk group and 184 ( 80.35 % ) were in the low-risk group. Epileptic seizures mainly occurred in the induction remission period ( 24.02 % ), maintenance treatment period ( 25.33 % ) and after bone marrow transplantation ( 21.40 % ). The common causes were MTX-related demyelinating encephalopathy ( 34.06 % ) and reversible posterior encephalopathy syndrome ( PRES ) ( 25.3 % ). The first symptom was mainly convulsion ( 34.50 % ). The first attack had a comprehensive attack and partial attack. Most patients stop themselves. 30 cases ( 13.10 % ) had acute recurrence of epilepsy ( recurrence within three months after the first attack ), and 49 cases ( 25.76 % ) had neurological dysfunction after follow-up. 36 cases developed symptomatic epilepsy. Among the 130 children who completed the follow-up, 78 ( 60.00 % ) had no obvious neurological sequelae, and 52 ( 40.0 % ) had neurological sequelae. Among the 52 cases, there were 34 cases of mild sequelae and 18 cases of severe sequelae, including 8 cases of epilepsy combined with cognitive impairment. Conclusion: Epileptic seizure is a common neurological complication during ALL treatment. The etiology and associated manifestations of the first epileptic seizure are diverse. Early neuroimaging and EEG examination are helpful for early diagnosis and treatment.